Worship with teenagers : adolescent spirituality and congregational practice - Mathis, Eric L. (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2022)
"Addresses the vital role of public Christian worship in adolescent spiritual formation and shows how important youth ministry and worship ministry are to each other"--
Includes bibliographical references (pages 224-235) and index.
Keywords: Christian teenagers -- Religious life; Spiritual formation; Public worship; Church work with teenagers